Efisiensi Pompa Hidrolik untuk Aktuator Pintu Sterilizer di PT. Torus Ganda Tambusai Timur - Dongoran, Firdaus. H.; Silitonga, Nelson (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
PKS PT. Torus Ganda Tambusai Timur, located in Tambusai Village, Tambusai District, Rokan Hulu Regency, is a palm oil factory that produces Crude Palm Oil (CPO) with a production capacity of 60 tons of FFB per hour. The processing processes at this PKS include weighing, boiling, pressing, pulverizing, refining, and extracting the core at PKS PT. East Tambusai Double Torus, the Sterilizer used is a Horizontal Sterilizer, which has an elongated cylinder shape and is positioned horizontally using lorry transportation to transport fresh fruit bunches. The boiling process uses saturated steam with a three-peak boiling system. This research aims to determine the efficiency of the hydraulic pump needed to move the actuator on the Sterilizer door at PT. East Tambusai Double Torus. The object of this research is the Horizontal Sterilizer at PKS PT. East Tambusai Double Torus focuses on determining the efficiency of the hydraulic pump needed to drive the actuator on the Sterilizer door and maintaining the hydraulic pump. The conclusion of this research shows that maintenance is essential in a factory because it helps manage company expenses. After observations and discussions, the efficiency of the hydraulic pump in moving the actuator on the sterilizer door was obtained at 86%.